An international survey of speciality training in oral and maxillofacial pathology. (20th September 2013) - Hunter, Keith; Speight, Paul; Wright, John; van, Willie; Rich, Alison; Franklin, Christopher
<x xml:space="preserve">Abstract</x> Background Speciality training in oral and maxillofacial pathology (OMFP) across the world would be aided by guidance on a generic curriculum and training programme that all countries could use as a template. In order to facilitate this, we require an understanding of the various forms which OMFP training takes across the world. Methods We sent a questionnaire to OMF pathologists in the 42 countries represented in the IAOP membership, via their Regional Councillor. The questionnaire included detailed demographics, entry requirements, specialty training program and facilities/resources. Results Replies were received from 22/42 countries (52%). OMFP is a dental/dental and medical speciality in 72%, and in 92% of those, this is recognised by a licensing board. Training was undertaken in an academic environment in 85% (with many offering a further academic qualification) and the median length of training was 4 years. General/anatomical pathology training is mandated in 85% of programs and a common core of general sub‐specialities was identified. An end of training assessment was conducted in 80% of programs with most including written, practical and oral elements. Training program directors and educational supervisors were in place in 12/16 programs and, in most, Quality Assurance of training was externally monitored. In only one country was the number of trainees linked to workforce planning. Conclusions Training in OMFP varies across the world. However, we feel there is sufficient commonality for the development of an agreed indicative framework on education and training in Oral and Maxillofacial Pathology, perhaps under the auspices of the IAOP.